Pengembangan Media Pembelajaran Interaktif Menggunakan Power Point Dengan Audio Visual Untuk Materi Determinan Matriks - Cicilia Puji Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Since March 14, 2020, the city of Surakarta has been declared an Extraordinary Event (KLB) of the CoViD-19 corona virus. The world of education, including the University of Surakarta, maintains teaching and learning activities using an online learning system (online) or also known as distance lectures. This condition forces lecturers and students to be ready to face teaching and learning activities outside the habit of face-to-face, namely through distance lectures. The obstacles experienced by students with long-distance lectures include limited internet quota, poor signal in the area, not all students have cellphones. Distance lecturing also raises new problems for lecturers, how to convey material so that students can understand it well. The platform for online teaching and learning activities implemented at the University of Surakarta is whatsapp and google classroom. This media provides facilities for lecturers to deliver material in writing, without being able to deliver it orally. Researchers are moved to try to create or develop interactive learning media with simple audio visuals that can be uploaded through these media and make it easier for students to understand the material provided. The development of this learning media uses power point software equipped with audio visuals that are clear, simple and of sufficient size in the hope that students are able to download the material without any constraints, and can improve students' ability to understand the determinant matrix material. The researcher carried out the stages by collecting data, analyzing data, analyzing needs, making designs, making learning media, conducting trials, and implementing the learning media. Making learning media with the display created is the front page, menu display, determinant material, order 2 matrix determinant, order 3 matrix determinant, calculating determinants with Laplace expansion. Make an audio-visual explanation of the material clearly, then combine the audio visual with the material that has been made. Then conduct trials and implement these media to students of the Surakarta University Computer System Study Program who take Linear Algebra and Matrix courses. Researchers have produced power point based learning media products with audio visuals for the determinant matrix material. To find out student responses, researchers distributed questionnaires to students and obtained data that from the 17 questionnaire forms Return 15 questionnaire forms and all of them responded that the learning media was good, clear, simple and easy to understand. Learning using these media has increased students' understanding of the determinant material of the matrix, this is indicated by an increase in student quiz scores compared to when learning has not used this learning media.